Tests of anomalous quartic couplings at the Next Linear Collider - Éboli, O. J P [UNESP]; Gonzalez-Garcia, M. C. [UNESP]; Mizukoshi, J. K. (American Physical Society (APS), 1998)
We analyze the potential of the Next Linear e+e- Collider to study anomalous quartic vector-boson interactions through the processes e+e-→W+W-Z and ZZZ. In the framework of SU(2)L⊗U(1)Y chiral Lagrangians, we examine all effective operators of order p4 that lead to four-gauge-boson interactions but do not induce anomalous trilinear vertices. In our analysis, we take into account the decay of the vector bosons to fermions and evaluate the efficiency in their reconstruction. We obtain the bounds that can be placed on the anomalous quartic interactions and we study the strategies to distinguish the possible couplings.